Critical roles of p53 in epithelial-mesenchymal transition and metastasis of hepatocellular carcinoma cells. - Zheng Wang (Public Library of Science (PLoS), 2013)
Hepatocellular carcinoma (HCC) is one of the most malignant tumors and the biggest obstacle in curing HCC is its high metastasis potential. Alteration of p53 is the most frequent genetic change found in HCC. Although the biological function of p53 in tumor initiation and progression has been well characterized, whether or not p53 is implicated in metastasis of HCC is largely unknown. In this study, we analyzed the potential functions of p53 in epithelial-mesenchymal transition (EMT) and metastasis of HCC cells. Both insulin- and TGF-β1-induced changes of critical EMT markers were greatly enhanced by p53 knockdown in HCC cells. The insulin- and TGF-β1-stimulated migration of HCC cells were enhanced by p53 knockdown. Furthermore, in vivo metastasis of HCC cells using different mouse models was robustly enhanced by p53 knockdown. In addition, we found that p53 regulation on EMT and metastasis involves β-catenin signaling. The nuclear accumulation and transcriptional activity of β-catenin was modulated by p53. The enhanced EMT phenotype, cell migration and tumor metastasis of HCC cells by p53 knockdown were abrogated by inhibiting β-catenin signal pathway. In conclusion, this study reveals that p53 plays a pivotal role in EMT and metastasis of HCC cells via its regulation on β-catenin signaling.